Assessment of the Treatment Outcomes of Dome-shaped Proximal Tibial Osteotomy in Patients with Genu Varum Referred to Razi Hospital - Narimani, Aboozar (Asian Journal of Pharmaceutics (AJP), 2017)
Introduction: The proximal tibial osteotomy is an accepted and commonly used treatment for younger and active patients with medial unicompartmental osteoarthritis of the knee and varus deformity. The aim of this study was to assess the treatment outcomes of dome-shaped proximal tibial osteotomy in patients with genu varum. Materials and Methods: In this prospective study, dome-shaped osteotomy was performed in 23 patients (14 males and 9 females) with genu varus deformity that referred to Razi Hospital in Ahvaz in 2016. Patients were followed for 6 months after surgery and were assessed in terms of Modified Hospital for Special Surgery Knee Scoring System (HSSKS), tibiafemoral angle, Insall-Salvati index, and complications. Results: The mean tibiofemoral angle changed from 16.6 ± 5.01 varus to 6.9 ± 1.48 valgus degrees (P < 0.001). The mean modified HSSKS promoted from 73.3 ± 3.01 to 82.3 ± 1.45 (P < 0.001). Furthermore, there was no significant difference in the range of motion and quadriceps strength. Insall-Salvati index was not different significantly after dome-shaped osteotomy, and the mean patellar height index changed from 1.054 ± 0.07 to 1.057 ± 0.08 (P = 0.774). The incidence of complication after dome-shaped osteotomy was one case (4.34%) of non-union. Conclusion: Results of this study demonstrated that dome-shaped osteotomy of proximal tibial is a simple, safe, and useful treatment which has favorable results in patients with genu varum.